TUNNELING MAGNETORESISTANCE OF A NORMAL METAL/FERROMAGNETIC INSULATOR/FERROMAGNETIC HETEROSTRUCTURE - Wongwai, Warintorn; Jantayod, Aek (PSRU Journal of Science and Technology, 2021)
This work calculated the tunneling magnetoresistance resistance (TMR) of a normal metal/ferromagnetic insulator/ferromagnetic (N/FI/FM) junction by using the scattering method and the free-electron approximation in one dimensional system. It was found that the TMR can be enhanced when either barrier high or the thickness of ferromagnetic insulator increased. In addition, the ferromagnetic insulator with a large exchange coupling energy can also increase TMR. This result can be developed or designed the spintronics device in future.